Analyzing stress concentration factor in finite plate with different polygonal discontinuities under uniaxial compression using FEM - Patel, Rashmiben H.; Patel, Bhaveshkumar P. (Penerbit Universiti Kebangsaan Malaysia, 2023)
A geometric, or theoretical, stress-concentration factor is the ratio of the actual maximum stress at the discontinuity to the nominal stress. Stress concentrations occur when there are irregularities in the geometry or material of a structural component that cause an interruption to the flow of stress. This arises from such details as holes, grooves, notches, and fillets. A detailed understanding of the stress concentration around the hole is essential for optimal design and resilience to mechanical failure. Therefore, in the design of structures, it is essential to study the effects of polygonal discontinuities in structures to achieve convenient and efficient designs. The current paper investigated the stress concentration factor around the polygonal holes in the finite structural steel plate, assuming a plane stress state and uniaxial compression loading. The present study provides a complete finite element analysis of stress concentrations in structural steel plates with polygonal cutouts (triangular, square, pentagonal, and hexagonal), in contrast to the side ratio of a polygonal hole, and the length, and height ratio of a square hole. The increasing order of stresses and SCF are square, triangular, pentagonal, and hexagonal. Due to the more edges of polygonal shapes parallel to the loading direction and minimum corners positioned in the direction of loading, a square-shaped hole produces 40% less SCF than a hexagonal-shaped hole.